SpatiaLite, un innovativo spatial DBMS (GEOmedia, 2010)
SpatiaLite, an innovative open source DBMSFor a long time PostgreSQL/PostGIS have represented the high end Open Source Spatial DBMS: PostGIS implements a sophisticated client-server architecture, and this sometimes introduces an undesirable complexity. SpatiaLite is an extension module for SQLite, implementing the full OGC-SFS function set: this allows the deployment of a really light-weight but powerful Spatial DBMS. SpatiaLite is quickly gaining support and integration in mainstream open source GIS.